ABOUT THE RELATIVIZATION OF CENTRAL BANKS’ IMMUNITY IN CONTEMPORARY MONETARY LAW - Dimitrijević, Marko B. (Zbornik radova Pravnog fakulteta u Novom Sadu, 2025)
The subject of the analysis in the paper is to determine the characteristics and methods of implementing central bank immunity in the international monetary order, which in the circumstances of complex geopolitical relations in the world is no longer an untouchable concept of modern monetary legislation. In this sense, the paper starts with the hypothesis that restrictions in defining central bank immunity must be legally based and applied in the most restrictive way by the monetary legislator, as they can have far-reaching repercussions on the postulates of institutional, financial and functional independence in the work of central banks as guardians of monetary sovereignty. The research in the first part of the paper deals with the problem of normative regulation of legal protection in the work of central banks in a comparative environment. At the same time, the rest of the text discusses the concept of the so-called fundamental rights of central banks. The subject of special attention of the author is the identification of the legal basis and consideration of the scope of financial sanctions in the operations of central banks. By applying the dogmatic, axiological, and comparative methods, the author seeks to point out the most significant dilemmas of the monetary legal aspects of narrowing the immunity of central banks and their implications for the preservation of monetary stability as a global public good.